How to Use Natural Experiments to Estimate Misallocation - Sraer, David; Thesmar, David (American Economic Review, 2023)
We propose a method to estimate the effect of firm policies (e.g., bankruptcy laws) on allocative efficiency using (quasi-)experimental evidence. Our approach takes general equilibrium effects into account and requires neither a structural estimation nor a precise assumption on how the experiment affects firms. Our aggregation formula relies on treatment effects of the policy on the distribution of output-to-capital ratios, which are easily estimated. We show this method is valid for a large class of commonly used models in macrofinance. We apply it to the French banking deregulation episode of the mid- 1980s and find an increase in aggregate TFP of 5 percent. (JEL G21, G24, G28, G31, G32, H25)